A risk-prediction score for colorectal lesions on 12, 628 participants at high risk of colorectal cancer. (9th February 2022) - Liang, Lixin; Liang, Yingru; Li, Ke; Qin, Pengzhe; Lin, Guozhen; Li, Yan; Xu, Huan; Wang, Suixiang; Jing, Qinlong; Liang, Boheng; Xu, Lin
Abstract: Background: The uptake of colonoscopy is low in individuals at risk of colorectal cancer (CRC). We constructed a risk-prediction score (RPS) in a large community-based sample at high risk of CRC to enable more accurate risk stratification and to motivate and increase the uptake rate of colonoscopy. Methods: A total of 12, 628 participants classified as high-risk according to positivity of immunochemical fecal occult blood tests or High-Risk Factor Questionnaire underwent colonoscopy. Logistic regression was used to derive a RPS and analysed the associations of the RPS with colorectal lesions, giving odds ratios (ORs) and 95% confidence intervals (CIs). Results: Of the participants, men (OR = 1.73, 95% CI = 1.58–1.90), older age (≥65 years; 1.41, 1.31–1.53), higher body mass index (≥28 kg/m 2 ; 1.22, 1.07–1.39), ever smoking (1.47, 1.31–1.65), and weekly alcohol use (1.28, 1.09–1.52) were associated with a higher risk of colorectal lesions. We assigned 1 point to each of the above five risk factors and derived a RPS ranging from 0 to 5, with a higher score indicating a higher risk. Compared with a RPS of 0, a RPS of 1, 2, 3, and 4–5 showed a higher risk of colorectal lesions, with the OR (95% CI) being 1.50 (1.37–1.63), 2.34 (2.12–2.59), 3.58 (3.13–4.10), and 3.91 (3.00–5.10), respectively. The area under the receiver-operating characteristic curve of RPS in predicting colorectal lesions was 0.62. Conclusions: Participants with an increase in the RPS of ≥1 point had a significantly higher risk of colorectal lesions, suggesting the urgency for measuring colonoscopy in this very high-risk group. High-risk strategies incorporating RPS may be employed to achieve a higher colonoscopy-uptake rate.